Amino‐group excites vitality in nitrogen‐rich energetic salts of triazolium. Issue 1 (3rd November 2022) - Li, Junyan; Wu, Jinting; Zhao, Tingxing; Li, Hongbo; Zhang, Jianguo
Abstract: Incorporating amino groups is an efficient strategy for the tuning properties of energetic materials. However, there is no unanimous conclusion on the effect of the number of amino groups (−NH2 ) on performance. Therefore, in this study, different number of −NH2 of four energetic salts of triazolium based on oxadiazole and triazole were designed and synthesized. The structure features of energetic salts 4 –6 were then investigated by single‐crystal X‐ray diffractions and Hirshfeld surfaces analyses. Afterward, the effects of −NH2 were evaluated by thermal stability, impact sensitivity and detonation performance. All these energetic salts were insensitive to mechanical stimulation (IS >40 J), but the thermal decomposition temperatures of energetic salt 5 –7 with −NH2 are 24 °C to 54 °C higher than energetic salt 4 without −NH2 . Moreover, energetic salt 5 with one −NH2 has the highest theoretical detonation properties compared to those without −NH2 (4 ) and with two −NH2 (6, 7 ). These observations revealed that appropriate amount of −NH2 can lead to desirable increase in the energetic properties, and this work can offer guidance for the design and synthesis of further energetic salts. Abstract :